2022
DOI: 10.1038/s41598-022-07847-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential zones for rainwater harvesting interventions for sustainable intensification in the semi-arid tropics

Abstract: Decentralized rainwater harvesting (RWH) is a promising approach to mitigate drought in the drylands. However, an insufficient understanding of its impact on hydrological processes has resulted in poor resource planning in this area. This study is a meta-analysis of 25 agricultural watersheds representing a range of rainfall and soil types in the semi-arid tropics. Rainfall-runoff-soil loss relationship was calculated at daily, monthly and yearly levels, and the impact of RWH interventions on surface runoff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Trends in the current climate indicate more extreme rainfall events (e.g., Grusson et al, 2021), and the synergetic effects of multiple weather events (so-called compound events) call for improved knowledge of landscape responses to various events and their interactions at local scale (Zscheischler et al, 2018). The change of pulse events will require new approaches in data collection and hydrological modelling; moreover, complementary studies at various scales are needed to understand the impacts and, e.g., design of mitigation measures (e.g., Garg et al, 2022). Furthermore, although data might be available at high spatial resolution, the temporal scale of input parameters for modelling short-term events might be too coarse to match the means, an issue to discuss, e.g., when linking landscape hydrology with short-term weather events.…”
Section: Implications Of Higher Resolution Spatial Soil Physical and ...mentioning
confidence: 99%
“…Trends in the current climate indicate more extreme rainfall events (e.g., Grusson et al, 2021), and the synergetic effects of multiple weather events (so-called compound events) call for improved knowledge of landscape responses to various events and their interactions at local scale (Zscheischler et al, 2018). The change of pulse events will require new approaches in data collection and hydrological modelling; moreover, complementary studies at various scales are needed to understand the impacts and, e.g., design of mitigation measures (e.g., Garg et al, 2022). Furthermore, although data might be available at high spatial resolution, the temporal scale of input parameters for modelling short-term events might be too coarse to match the means, an issue to discuss, e.g., when linking landscape hydrology with short-term weather events.…”
Section: Implications Of Higher Resolution Spatial Soil Physical and ...mentioning
confidence: 99%
“…The Inverse Distance Weight (IDW) interpolation technique was employed to estimate rainfall in areas without direct measurements. Researchers [46] reported that a mean annual rainfall of 150-750 mm/year was suitable for most RWH techniques to be effective, and [47] reported that a cumulative annual rainfall of 200-300 mm in the Indian semi-arid tropics was necessary to initiate surface runoff for rainwater storage. Based on these findings, annual rainfall in the study area was classified into three categories, including a low range with minimum significance for RWH structures < 400 mm ranked '1', medium annual rainfall range 400-700 mm assigned '2', and rainfall > 700 mm ranked '3'.…”
Section: Rainfallmentioning
confidence: 99%
“…Amidst ongoing unsettling events, including a global pandemic and a war in Ukraine, the challenge of sustainability remains central 1 , 2 . In addition, there are many problems related to health, human rights and the environment, including malnutrition and food insecurity 3 , as well as water shortage 4 , 5 . The Sustainable Development Goals (SDGs) offer a pathway to reconciling economic growth with environmental concerns, through a highly interconnected framework of analysis 6 .…”
Section: Introductionmentioning
confidence: 99%